Low-cost central monitor based personal computer with electrocardiogram and heart rate parameters via wireless XBee Pro - Bambang Guruh Irianto; Anita Miftahul Maghfiroh (Universitas Ahmad Dahlan, 2023)
Heart rate signals and electrocardiograms are crucial indicators of a person’s health, particularly for individuals in intensive care units (ICU). The goal of this study is to wirelessly use a central monitoring system to continually and in real-time monitor the electrocardiogram signal and heart rate. The result of this research is that a wireless system can transmit continuous, distant, and real-time electrocardiogram and heart rate readings. Two transmitters and two receivers were used to send the signal in real-time. Lead II was used to capture the electrocardiogram (ECG) data, which was then processed by a microprocessor to determine the heart rate in beats per minute. The XBee Pro wireless was then used to transmit the data to the monitor in the form of an electrocardiogram and heart rate signal. The results of the XBee wireless performance test with statistics for determining heart rate value revealed that there was no discernible difference in the average value at a distance of 8, 10, 25, and 30 meters (P-value > 0.05). According to the study’s findings, wireless transmission is feasible over a limited distance and in real-time. Hospitals can use a central monitor to implement this research.